ANALISIS PENGARUH DIFERENSIASI PRODUK, CITRA MEREK, PREFERENSI MEREK TERHADAP KEPUTUSAN PEMBELIAN - Nurzaini, Yusuf; Khasanah, Imroatul (Diponegoro Journal of Management, 2018)
This research is based on the phenomenon of the emergence of various new brands, especially for motorcycle matic category. Currently the market share of motorcycles matic controlled by yamaha mio. This indicates the increasingly tight competition in world sales of motorcycles in seizing the market. This study aims to examine the effect of product differentiation variables, brand image and brand preference on motor Matic Yamaha mio purchasing decision in Semarang city.The number of samples of 100 respondents was taken by purposive sampling technique. Data analysis method used is multiple regression analysis, where the analysis include: validity test, reliability  test,  classic  assay  test,  linear  regression  test  bergannda,  t  test,  F  test,  test  of determination.The result of multiple regression analysis showed that all independent variables of product differentiation (0,273), brand image (0,330) and brand preference (0,284) have positive and significant relation to dependent variable that is purchasing decision.